Characterizing the utilization of doula support services among birthing people of color in the United States: a scoping review - Emily Kang; Nat'e Stowe; Kelsey Burton; Tiarney D. Ritchwood (BMC, 2024)
Abstract Background Birthing people of color experience disproportionately higher rates of infant and maternal mortality during pregnancy and birth compared to their white counterparts. The utilization of doula support services may lead to improvements in the birthing experiences of birthing people of color. Yet, the research in this area is sparse. Thus, the purpose of this review is to characterize the research on doula utilization among birthing people of color, identify gaps in the field, and provide recommendations for future research. Methods Utilizing PRISMA guidelines, we conducted a scoping review, searching PubMed, PsycINFO, CINAHL, and Google Scholar for peer-reviewed articles published between January 1, 2016, to July 3, 2022. Results Twenty-five articles met inclusion criteria. We identified the three themes characterizing included studies: (1) how doulas support (HDS) their clients, (2) doula support outcomes (DSO), and (3) considerations for implementing doula support services (CIDS). Despite doulas being described as agents of empowerment, and providing social support, education, and advocacy, birthing people of color reported low utilization of doula support services and findings regarding their effectiveness in improving birthing outcomes were mixed. Conclusions While some studies suggest that doulas may offer important services to birthing people of color, doulas are largely under-utilized, with many birthing people reporting low knowledge of their potential roles during the pre- and post-partum periods. Moreover, few studies were designed to assess intervention effects, limiting our ability to draw firm conclusions. Birthing people of color are at elevated risk for maternal mortality. As such, interventions are needed to support this population and improve outcomes. Our review suggests that, while doulas have the potential to make important contributions to the birthing support team, they are underutilized, and intervention studies are needed to enable estimates of their true effectiveness.